The Morphology of Hydroxyapatite Nanoparticles Regulates Cargo Recognition in Clathrin-Mediated Endocytosis - Zhu, Cheng; Zhou, Xuejie; Liu, Ziteng; Chen, Hongwei; Wu, Hongfeng; Yang, Xiao; Zhu, Xiangdong; Ma, Jing; Dong, Hao (Frontiers in Molecular Biosciences, 2021)
The clathrin-associated protein adaptin-2 (AP2) is a distinctive member of the hetero-tetrameric clathrin adaptor complex family. It plays a crucial role in many intracellular vesicle transport pathways. The hydroxyapatite (HAp) nanoparticles can enter cells through clathrin-dependent endocytosis, induce apoptosis, and ultimately inhibit tumor metastasis. Exploring the micro process of the binding of AP2 and HAp is of great significance for understanding the micro mechanism of HAp's anti-cancer ability. In this work, we used molecular modeling to study the binding of spherical, rod-shaped, and needle-shaped HAps towards AP2 protein at the atomic level and found that different nanoparticles' morphology can determine their binding specificity through electrostatic interactions. Our results show that globular HAp significantly changes AP2 protein conformation, while needle-shaped HAP has more substantial binding energy with AP2. Therefore, this work offers a microscopic picture for cargo recognition in clathrin-mediated endocytosis, clarifies the design principles and possible mechanisms of high-efficiency nano-biomaterials, and provides a basis for their potential anti-tumor therapeutic effects.